Basic Education Financing Standards and Issues Related to Basic Education Financing - Cantika Salsabila; Rizki Ananda; Larasati Sekar Kinanthi; Rinellia Silvia (Universitas Muhammadiyah Enrekang, 2023)
Funding for basic education is the responsibility of the government which guarantees the fulfillment of education in the national education system as a human right in the field of education. This research aims to analyze the standard of financing for basic education and the problems related to financing for basic education. This research method is a qualitative method with a literature study approach that will be analyzed descriptively. The results of this study are that in practice there are still problems in financing governance in Indonesia, especially educational autonomy that is not evenly distributed in terms of providing budgets for developing academic qualifications and improving the quality of teachers. Meanwhile, the existing problem is that the government's education programs are currently not running optimally due to differences in basic education financing standards but are not in line with the distribution of educational services which is affected by education funding, especially for regions that are . The implication is that education funding from funding allocations can be given evenly to be regulated and allocated according to its use so that it can run effectively and efficiently so that basic education in Indonesia can progress and develop